ChemInform Abstract: Synthesis of Imidazo[1, 2‐f]phenanthridines Through Palladium‐Catalyzed Intramolecular C—C Bond Formation. Issue 16 (March 2016) - Saini, Hitesh Kumar; Dhiman, Shiv; Pericherla, Kasiviswanadharaju; Kumar, Anil
Abstract: The synthesis is based on the multicomponent reaction of 1, 2‐dicarbonyl compounds, anilines, aldehydes and ammonium acetate to 2‐(2‐bromoaryl)‐1, 4, 5‐triaryl‐1H‐imidazoles which are cyclized to the title products.